2014
DOI: 10.1063/1.4903295
|View full text |Cite
|
Sign up to set email alerts
|

Probing hot-electron effects in wide area plasmonic surfaces using X-ray photoelectron spectroscopy

Abstract: Plasmon enhanced hot carrier formation in metallic nanostructures increasingly attracts attention due to potential applications in photodetection, photocatalysis, and solar energy conversion. Here, hot-electron effects in nanoscale metal-insulator-metal (MIM) structures are investigated using a non-contact X-ray photoelectron spectroscopy based technique using continuous wave X-ray and laser excitations. The effects are observed through shifts of the binding energy of the top metal layer upon excitation with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The absolute value as well as the sign of this potential will be affected by the deviation between the excitation frequency and the SPR frequency. Promisingly, the discovery of the plasmoelectric potential defies the photon-energy limitation of the photoelectric conversion process, and has increasingly attracted researcher’s focal interest. Via the introduction of a well-defined thermodynamic model, A. Polman and co-workers have discovered that the charge transfer in plasmoelectric potential is dictated by the principle of minimal free energy under steady state excitations . M. Moskovits et al have reported that, owing to this plasmoelectric effect, gold nanoparticles can change their charge states when the UV–visible spectrum is measured .…”
mentioning
confidence: 99%
“…The absolute value as well as the sign of this potential will be affected by the deviation between the excitation frequency and the SPR frequency. Promisingly, the discovery of the plasmoelectric potential defies the photon-energy limitation of the photoelectric conversion process, and has increasingly attracted researcher’s focal interest. Via the introduction of a well-defined thermodynamic model, A. Polman and co-workers have discovered that the charge transfer in plasmoelectric potential is dictated by the principle of minimal free energy under steady state excitations . M. Moskovits et al have reported that, owing to this plasmoelectric effect, gold nanoparticles can change their charge states when the UV–visible spectrum is measured .…”
mentioning
confidence: 99%
“…Similarly, XPS has also been used to survey hot electron effects in wide plasmonic areas [ 156 , 157 ] while also providing insights into the evolution of the energy band structure of the Schottky junctions that are widely used in plasmonic photocatalysis ( Figure 9 ).…”
Section: Probing Hot Electronsmentioning
confidence: 99%